Hazards at work : organizing for safe and healthy workplaces (London, 2007)
"The completely revised and up-dated second edition of the TUCs best-selling guide to health and safety at work in its popular new book format – indispensable for union reps and safety practitioners. Includes fully rewritten chapters on smoking and asbestos, and updates on relevant statutes, including the new Corporate Manslaughter Act. "